(untitled) (JS (JURNAL SEKOLAH), 2020)
Abstract: Learning Model Welcomes the New Era of Normal in Early Childhood Institutions in Riau. The most difficult challenge for parents with the downward condition of Covid-19, of course, is the decline in their economic capacity. This can affect the attitudes and behavior of parents in supervising, guiding, training, and giving attention to their children. The dynamics that hit mainly the elderly with middle to lower economic level with the existence of the Covid-19 pandemic, it is very difficult to survive to meet the needs of daily life. Such conditions are a concern for all of us, hopefully the golden age children as part of the successor movement will continue to grow and develop as the nation’s capital and assets in future development. Keywords: Learning Model, New Era Life, Early Childhood Institutions Abstrak : Model Pembelajaran Menyongsong New Era Normal Pada Lembaga Paud di Riau. Tantangan terberat bagi para orang tua dengan kondisi merebahnya Covid-19 tentunya mempengaruhi penurunan kemampuan ekonomi mereka. Hal tersebut dapat mempengaruhui sikap dan perilaku orang tua dalam mengawasi, membimbing, melatih, serta memberikan perhatian terhadap anak-anak mereka. Dinamika yang melanda utamanya para orang tua dengan tingkat ekonomi menengah ke bawah dengan adanya pandemi Covid-19 ini, sangat sulit bertahan untuk mencukupi kebutuhan hidup sehari-harinya. Kondisi yang demikian menjadi keprihatinan kita semua, semoga para anak usia emas sebagai bagian dari gererasi penerus tetap dapat tumbuh dan berkembang sebagai modal dan aset bangsa dalam pembangunan di masa mendatang. Kata Kunci : Model Pembelajaran, New Era Life, Lembaga Paud